ST2: the biomarker at the heart of GVHD severity - Ito, Sawa (Blood, 2015)
In this issue of Blood, Ponce et al report that high suppression of tumorigenicity 2 (ST2) levels are significantly associated with the incidence of acute graft-versus-host disease (aGVHD) and transplant-related mortality (TRM) in recipients of double-unit cord blood transplants (CBTs).(1)